A comparison of intimate partner and other sexual assault survivors’ use of different types of specialized hospital-based violence services - Du Mont, Janice (BMC Womens Health, 2017)
BACKGROUND: Little is known about the health service utilization of women sexually assaulted by their intimate partners, as compared with those sexually assaulted by other perpetrators. To address this gap, we describe the use of acute care services post-victimization, as well as a broad range of survivor and assault characteristics, across women assaulted by current or former intimate partners, other known assailants, and strangers. METHODS: Information was gathered from individuals presenting to 30 hospital-based sexual assault and domestic violence treatment centres using a standardized data collection form. We examined the data from 619 women 16 years of age or older who were sexually assaulted by one assailant. RESULTS: Women sexually assaulted by a current or former intimate partner were less likely than those assaulted by another known assailant or a stranger to have been administered emergency contraception (p < 0.001) or prophylaxis for sexually transmitted infections (p < 0.001), and counselled for potential use of HIV post-exposure prophylaxis (p < 0.001). However, these women were more likely than those in the other two groups to have had their injuries documented with photographs (p < 0.001), have undergone a risk assessment (p = 0.008), and/or have engaged in safety planning (p < 0.001). CONCLUSIONS: Women sexually assaulted by current or former intimate partners utilized services offered by sexual assault and domestic violence treatment centres differently than those assaulted by other known assailants and strangers. This may reflect their different health, forensic, and social needs, as well as the importance of offering care tailored to their particular circumstances. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12905-017-0408-9) contains supplementary material, which is available to authorized users.